PENGARUH RASIO PROFITABILITAS TERHADAP KESEHATAN PERMODALAN BANK SWASTA NASIONAL DI BEI - EVELINA, ENNY (Berkala Ilmiah Mahasiswa Akuntansi)
Bad performance of the national banking system is considered to contribute the emergence of the financial crisis in Indonesia. One measure to look at the health of banks is through CAR. CAR is the most important indicator according to Bank Indonesia in maintaining the health of the bank. The research design is quantitative with the hypothesis. Object of study is a national private banks listed on the Indonesia Stock Exchange. The variables used in this research is the return on equity (ROE), return on assets (ROA), net profit margin (NPM) and its capital adequacy ratio (CAR). The period of study for 5 years from 2007-2011. The type of data used is quantitative data obtained from the IDX website. Data analysis techniques using multiple linear regression. The results showed that (1) profitability ratio is had positive influence to capital adequacy ratio only Net profit margin and (2) profitability ratio which is not a positive effect on capital adequacy ratio is Return on assets and return on equity.